Mobile Learning Management System - Mohd Syafiq Bin Mahayudin, Mohd Syafiq (Universiti Teknologi PETRONAS, 2012)
Mobile technology can help to connect people with information faster despite of their location. The author decided to enhance the current Learning Management System by integrating mobility element into it. Mobile Learning Management System (MLMS) is designed to facilitate the communication between parents and teachers which is different from the existing Learning Management System that offered in the market. MLMS is a proposed solution to solve the problems faced by the school and parents as there is less communication between parents and teachers, parents have limited updates regarding their children’s academic performance and also time and distance barrier hinder parents to involve actively in their children’s schooling. This is due to the mobility and functionality of MLMS that provide two ways communication between parents and teachers. Apart from that, this system provides parents with examination records, attendance records and also disciplines records of their children. The objective of this project is to create a Mobile Learning Management System that can facilitate two ways communication between parents and teachers. The application been developed using Rapid Application Development methodology. Android has been chosen as the mobile platform to optimize the capability of the Android technology and to leverage on its market potential.